The causal relationship between obesity, obstructive sleep apnea and atrial fibrillation: a study based on mediated Mendelian randomization - Li, Tianyu; Rong, Li; Gao, Yanlin; Cheng, Wei (Frontiers in Cardiovascular Medicine, 2024)
This study employed a two-sample and multivariate Mendelian randomization (MR) approach to evaluate the mediating role of obstructive sleep apnea (OSA) in the link between obesity and atrial fibrillation (AF). The findings revealed that obesity heightened the risk of OSA, and OSA substantially increased the risk of AF. The mediated MR analysis demonstrated that OSA plays a part in the causal relationship between obesity and AF, with approximately 6.4% of the AF risk being mediated by OSA. This investigation utilized GWAS data on AF and OSA, and obesity data from the Finngen database. The methodologies employed included inverse variance weighted meta-analysis, MR-Egger regression, weighted median, simple model, and weighted model. Additionally, sensitivity analyses were conducted to evaluate heterogeneity and potential bias. This study underscores the potential of MR as a novel approach to explore biomedical causality. The outcomes of this study enhance comprehension of the correlation between obesity, OSA, and AF and offer new insights for the prevention and treatment of AF.